PENGARUH MEDIA WORDLESS BOOK TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5–6 TAHUN - Aulia Maulidia Arliana; Ruqoyyah Fitri; Nur Ika Sari Rakhmawati; Eka Cahya Maulidiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking ability is one of the important aspects of early childhood language development. However, there are still several children aged 5–6 years who experience difficulties in expressing ideas, lack confidence when speaking, tend to be passive in social interactions, and have limitations in vocabulary usage and word pronunciation. These problems indicate the need for interesting and interactive learning media to help improve children’s speaking skills. One of the learning media that can be used is a wordless book, which is a book without text containing only pictures or illustrations that encourage children to speak and retell stories based on their imagination. This study aims to determine the effect of wordless book media on the speaking ability of children aged 5–6 years. This study used a quantitative approach with an experimental research type employing a One Group Pretest-Posttest Design. The subjects of this study were children aged 5–6 years in Group B at the kindergarten where the research was conducted. Data collection techniques included observation, documentation, and speaking ability assessment sheets. The data were analyzed using statistical tests to determine the differences in children’s speaking abilities before and after the implementation of the wordless book media. The results of the study showed that the use of wordless book media had a positive effect on the speaking ability of children aged 5–6 years. Children became more active in speaking, more confident in expressing their opinions, better at using vocabulary, and more capable of expressing ideas and retelling stories based on the pictures they observed. Therefore, wordless book media can be used as an effective alternative learning medium to improve early childhood speaking skills.